Embodying combat: How boxers make sense of their 'conversations of gestures'. (December 2019) - Beauchez, Jérôme
This essay offers an ethnography of the 'conversations of gestures' that occur between boxers during training fights or 'sparring'. By showing how these situations are embodied, it elaborates a sociology of the senses and meaning as it relates to these ordeals. In addition to considering the boxers and their 'culture in interaction', the essay reexamines a number of the assumptions embraced by sociologists of 'habitus' and 'practical sense'. While a boxer's knowledge lies first and foremost in his fists, the fight also triggers a vital consciousness of the situation – a body image – that, when articulated with habitualized motor schemas, makes reflection and strategy central to the action itself. To deny the possibility of such boxing reflexivity would mean describing the fighter as a 'cultural dope' whose capacity for reflection is supplanted by the acquisition of fighting reflexes: this is what is entailed by the concept of 'boxing habitus'. Yet this emphasis on the body's automatic mechanisms reduces the sociology of practice to the socialization of body schemas, without being able to connect them to body images. The latter is what this essay seeks to reintroduce into analysis.